Pengaruh Workplace dan Manajemen Stres terhadap Burnout pada Perawat di Masa Pandemi Covid 19 - Mepy Nurana; Tasya Aspiranti; Sri Suwarsi (Syntax Corporation, 2023)
During the COVID-19 pandemic, nurses have a high risk of burnout, due to high work stress, workload, risk of COVID-19 infection, through close contact with patients. This study aims to analyze the effect of workplace factors and stress management on burnout in UPT Tarogong Health Center nurses during the COVID-19 pandemic. This research is a verifiative descriptive research, with a census sampling method or whole sampling, namely all nurses at UPT Puskesmas Tarogong. Primary data were collected through interviews and surveys using the Maslach Burnout Inventory questionnaire, Quick Burnout Assessment questionnaire, and stress management questionnaire. The workplace questionnaire for aspects of workload, control, reward, and fairness is at a sufficient level, while community values and values are at a high level, meaning that improvements are still needed in workload management, decision making, communication, and a more transparent reward system for nurses at UPT Puskesmas Tarogong. Nurses tend to use individual stress management methods, primarily using personal relaxation techniques as well as discussions with spouses or families to manage work stress levels. Burnout is at a considerable level that is characterized by a degree of depersonalization and a mild decrease in performance. Workplace and stress management affect the burnout of nurses UPT Puskesmas Tarogong, and the effect of workplace on burnout is greater than the influence of stress management so that improvements are needed in workload management, decision making, and effective communication with nurses, also workplace intervention and stress management are needed in Puskesmas to reduce the level of burnout, so management needs to implement a stress management program, both organizationally such as holding recreation for nurses, and it is necessary to divide the distribution of workload fairly and actively discuss with nurses.